ANALISIS PERBANDINGAN KINERJA JARINGAN VPN BERBASIS MIKROTIK MENGGUNAKAN PROTOKOL PPTP DAN L2TP SEBAGAI MEDIA TRANSFER DATA - Irnawan, Fahmi Dhimas; Triyono, Joko; k, Rr. Yuliana Rachmawati (Jurnal Jarkom, 2014)
ABSTRACTVirtual Private Network (VPN) is a computer networking technology which developed by the companys large-scale with network that connects other networks over the Internet using the path that requires privacy in communication. In VPN networks, the Internet is a media that becomes support facilities in the communication process. This case because the Internet becomes an access point to data transfer between different client location or location from VPN server.In the process of testing using three mechanisms analysis captured from the calculation of data transfer, video on demand, and reliability of access the website. The process of data transfer in a VPN network using FTP with 5 parameter files of different sizes in each file. Then the delay calculation using video on demand files saved on a server with a VPN client localhost with audio and video type of files. The reliability of access to the website using ping and trace route media. Differences between client location becomes an advantages with using a VPN network that is very useful to share data or resources. VPN network is also able to provide an alternative access to a website that is on the internal VPN server. So the website behind VPN server and accessed by the VPN client more closer than without using VPN. Keywords : VPN, encapsulation, data transfer